Athlete maltreatment in sport: Protocol for a scoping review - David M. Brown; Amy E. Nesbitt; Sasha Gollish; Tara-Leigh F. McHugh; Catherine M. Sabiston (PLoS ONE, 2025)
Research on maltreatment in sport demonstrates detrimental effects on athletes’ well-being, and recent news reports highlight the pervasiveness of this issue. However, inconsistencies in defining and operationalizing athlete maltreatment in sport have resulted in issues with conceptual clarity that limits current research, practice, and monitoring within and across sport sectors. This scoping review will synthesize the scientific literature on athlete maltreatment in sport and identify current knowledge gaps for research and practice. The review objectives are to: (1) map how maltreatment has been conceptualized and operationalized in the literature; (2) identify and describe the types of athlete maltreatment that have been investigated; and (3) explore current trends in research approaches and methods applied to the study of athlete maltreatment. An established six-stage scoping review methodology will be applied, as well as field-specific guidelines for community advisory group consultations. The protocol will be conducted over a one-year time frame and has been registered in advance ( https://osf.io/r7ycp/overview ). Relevant sources will be identified using a systematic search strategy across six electronic databases. Study screening procedures will occur in duplicate using pre-determined eligibility criteria. For inclusion, articles must address the concept of maltreatment among athletes (of any age, sport, or competition level), and contain original peer-reviewed research. Extracted data will be analyzed using qualitative content analysis and descriptive statistics. Preliminary results will be presented to community advisors (e.g., athletes, coaches, sport administrators, clinicians, policy writers, researchers) to contextualize findings and prioritize actionable recommendations to improve sport systems. Results will be published in a peer-reviewed journal and presented at academic conferences for sport leaders and researchers with the aim of informing measures, interventions, frameworks, and/or policies.